Supramolecular strategy for reducing the cardiotoxicity of bedaquiline without compromising its antimycobacterial efficacy. (September 2018) - Kuok, Kit Ieng; In Ng, Phoebe Choi; Ji, Xia; Wang, Chunming; Yew, Wing Wai; Chan, Denise P.C.; Zheng, Jun; Lee, Simon M.Y.; Wang, Ruibing
Abstract: Bedaquiline (BDQ) is a newly approved anti-tuberculosis drug in treating multidrug-resistant tuberculosis. However, it has very poor aqueous solubility and several case reports have proposed that BDQ has potential risk of cardiotoxicity to patients. In this present study, we have explored into employing host-guest interactions between a synthetic receptor, cucurbit[7]uril (CB[7]), and BDQ aiming to improve the solubility and reduce the inherent cardiotoxicity of BDQ. HPLC-UV test on the solubility of BDQ in the absence and in the presence of increasing concentrations of CB[7] suggested a host-dependent guest-solubility enhancements. Cardiovascular studies using an in vivo zebrafish model demonstrated that the cardiotoxicity of BDQ was indeed alleviated upon its complexations by the synthetic receptor. Furthermore, our in vitro antibacterial studies suggested that CB[7] formulated BDQ preserved its antimycobacterial efficacy against Mycobacterium smegmatis . Therefore, CB[7] may become a suitable pharmaceutical excipient in formulating BDQ for improving its physiochemical properties (such as solubility), and for alleviating its side effects (such as cardiotoxicity), while the antimycobacterial efficacy of BDQ may be well maintained. Highlights: The solubility of bedaquiline was improved by cucurbit[7]uril. The cardiotoxicity of bedaquiline was alleviated by cucurbit[7]uril. The antimycobacterial activity of bedaquiline was not affected by cucurbit[7]uril.